2019
DOI: 10.1002/cre2.183
|View full text |Cite
|
Sign up to set email alerts
|

Excessive computer use as an oral health risk behaviour in 18‐year‐old youths from Poland: A cross‐sectional study

Abstract: Background Many studies have indicated that the excessive use of computers (more than 3 hr/d) might be associated with an unhealthy life‐style. Aim The aim of this study was to evaluate the relationship between excessive computer use with the condition of the teeth and periodontium and the oral health behaviour of 18‐year‐olds. Design Cross‐sectional studies, using a questionnaire, were carried out on 1,611 18‐year‐olds from Poland. The questionnaire contained questions about socioeconomic status and informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For instance, a survey conducted among adolescents from 9 African countries reported sub-optimal tooth brushing among 22% and only 58% of the sample reported regular handwashing after using the toilet [ 31 ]. Some studies among adolescents have also reported an overlap between behaviors linked to communicable diseases and NCDs [ 32 , 33 ]. This behavioral overlap (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a survey conducted among adolescents from 9 African countries reported sub-optimal tooth brushing among 22% and only 58% of the sample reported regular handwashing after using the toilet [ 31 ]. Some studies among adolescents have also reported an overlap between behaviors linked to communicable diseases and NCDs [ 32 , 33 ]. This behavioral overlap (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, there was no significant relationship of video gaming or daily video gaming time with DMFT/S, dmft/s, while advanced caries lesions (ICDAS = 5 or 6) were found to be significantly more common in the daily video gamer group. Excessive use of computers (more than 3 h/day) in Polish adolescents (18‐year old) has been reported to be associated with increased frequency of unfilled cavities (according to DMFT), less healthy periodontium and risk of gingival bleeding 26 . Doitchinova et al 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested that excessive computer use was associated with less healthy periodontium, more bleeding on probing, and more untreated decay in permanent teeth among young adults from Poland [20]. However, the study addressed computer use in general and it is not known whether Internet addiction was associated with clinically assessed oral health outcomes [20].…”
Section: Introductionmentioning
confidence: 97%
“…Internet addiction was associated with a low frequency of tooth brushing, avoidance of dental checkups [ 8 , 17 , 18 ], and more self-reported gingival bleeding, tooth pain, and bad breath [ 18 , 19 ]. Previous research suggested that excessive computer use was associated with less healthy periodontium, more bleeding on probing, and more untreated decay in permanent teeth among young adults from Poland [ 20 ]. However, the study addressed computer use in general and it is not known whether Internet addiction was associated with clinically assessed oral health outcomes [ 20 ].…”
Section: Introductionmentioning
confidence: 99%